A Rare Tick Tale: A Novel Case of the Australian Paralysis Tick Causing Multiple Cranial Neuropathies - Sujan A. Surendran; Philomena McNamara; Jonathan N. Hyer; Charles S. Su (Case Reports in Ophthalmological Medicine)
The Australian paralysis tick (Ixodes holocyclus) is found along the east coast of Australia. Tick bites may result in paralysis ranging from muscular weakness to ascending paralysis requiring respiratory support. Ocular complications and facial nerve involvement are rare. We present a rare occurrence of tick-bite-associated visual loss, proptosis, and multiple cranial neuropathies not previously reported in the literature. The tick was removed, and the patient’s symptoms improved following treatment with steroids and oral doxycycline. The vision and sensory changes are not explained by the Ixodes toxin; thus, we hypothesize this is related to orbital apex inflammation.